Framed to be open: exploring the strategies of planning university campus in China - Ho, Jason; Anderson, Charles; Zakariya, Khalilah (Higher Education Press, Beijing, 2013)
In the quest for modernization, China has embarked upon the construction of new university campuses. These new campuses are often planned in a similar way to the 'Forbidden City', isolated from the surrounding context. Under this model, most of the university resources are arranged within the boundary walls and not allowed to be used by neighboring residents. This type of arrangement reinforces the politics of public-private separations and produces a discriminating urban policy of exclusion. While acknowledging the significance of boundary the paper speculates alternatives to the traditional master plan of university campus, through re-examining the current role of boundary in the bottom-up process and the production of shared resources. Instead of providing one-off design solutions, the alternatives re-examine a real-life condition as an evolving process and dynamic system through a set of strategies by which planners, urban designers, architects and landscape architects can use in redefining the boundary between public and private.